2016
DOI: 10.1021/acs.nanolett.5b03658
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Room-Temperature Ferromagnetic MnAs Segments on GaAs Nanowires via Sequential Crystallization

Abstract: Nanowire geometry and crystalline structure under Mn supply Figure S1(a) and S1(b) show scanning electron microscopy (SEM) images of regular, Mn-free GaAs nanowires, grown as a control experiment, and nanowires grown under (Ga,Mn)Assupply ( rst sample series described in the article). On both samples the wires display the same length, indicating that the supply of Mn does not inhibit the VLS growth mechanism.The only di erence visible in SEM concerns the catalyst droplet: solidi ed Ga-droplets are perfectly sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
2
15
0
3
Order By: Relevance
“…It has been shown by high-resolution transmission electron microscopy that this growth process leads to the formation of a well-defined hexagonal α-MnAs wurzite crystal at the tip of a predominantly wurzite GaAs NW, with an epitaxial relationship [0001]MnAs [0001]GaAs along the NW-axis [22]. As reported for bulk MnAs, the tip is in a hexagonal ferromagnetic α-phase up to the Curie temperature of about 313 K, above which it undergoes a structural phase transition into an orthorhombic paramagnetic β-phase [23].…”
Section: Arxiv:181010865v1 [Cond-matmes-hall] 25 Oct 2018mentioning
confidence: 99%
“…It has been shown by high-resolution transmission electron microscopy that this growth process leads to the formation of a well-defined hexagonal α-MnAs wurzite crystal at the tip of a predominantly wurzite GaAs NW, with an epitaxial relationship [0001]MnAs [0001]GaAs along the NW-axis [22]. As reported for bulk MnAs, the tip is in a hexagonal ferromagnetic α-phase up to the Curie temperature of about 313 K, above which it undergoes a structural phase transition into an orthorhombic paramagnetic β-phase [23].…”
Section: Arxiv:181010865v1 [Cond-matmes-hall] 25 Oct 2018mentioning
confidence: 99%
“…Similar to thin films, the most attention has been paid to the study of the growth of the NWs based on (Ga,Mn)As DMS. They have been obtained using a variety of catalysts for the growth, such as MnAs , Ga , Mn , as well as by overgrowth of wrapped shell on GaAs NWs and by Mn ion implantation . It should be noted, that usually the formation of (Ga,Mn)As shell carries out at lower temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the use of Ga or Mn assisted synthesis of (Ga,Mn)As NWs allows to increase the growth temperature and, as consequence, the crystalline quality of the structures. Nonetheless, for the NWs grown by Ga‐assisted molecular‐beam epitaxy (MBE), it was found that Mn atoms had been accumulated in the Ga droplet . Moreover, no significant incorporation of Mn atoms into the nanowire was observed , although residual doping level had not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Соединение MnAs обладает ферромагнетизмом с температурой Кюри немного выше комнатной (318 K), что делает его перспективным материалом для использования в различных элементах спиновой электроники, функционирующих в терагерцовом диапазоне [8][9][10].…”
unclassified